2022
DOI: 10.35502/jcswb.265
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing resilience: An interpretative phenomenological analysis of The Awe Project

Abstract: Awe is a complex emotion often associated with experiencing multiple other positive emotions during a  captivating and immersive experience. Engaging in awe experiences contributes to enhancing an individual’s personal resilience and well- being. Moreover, the benefits of experiencing awe transcend the individual, as it has been described as a self-transcendent emotion provoking concern beyond the self. Using an Interpretative Phenomenological Analysis (IPA) methodology, this exploratory paper evaluates the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(64 citation statements)
references
References 90 publications
4
15
0
Order By: Relevance
“…Finally, numerous participants explained the intensity related to awe experiences which can also result in them not being able to fully describe it. This is consistent with Keltner and Haidt's (2003) easy to explain, and mainly a positive experience (Dong and Ni, 2020;Thompson, 2022a).…”
Section: Defining and Understanding Awesupporting
confidence: 86%
See 2 more Smart Citations
“…Finally, numerous participants explained the intensity related to awe experiences which can also result in them not being able to fully describe it. This is consistent with Keltner and Haidt's (2003) easy to explain, and mainly a positive experience (Dong and Ni, 2020;Thompson, 2022a).…”
Section: Defining and Understanding Awesupporting
confidence: 86%
“…Guided by the existing research that has already established the relationship between awe, wellness, and resilience (Tabibnia, 2020;Thompson, 2022a), the focus of the interviews shifted more directly to the research question and specifically, the phenomenon of awe. The participants were asked to define awe in their own words, and this negotiator related it to beauty: Awe is something that is a beautiful thing, it's something that brings you to say "wow" or to feel amazed by some of these things that you're experiencing.…”
Section: Defining and Understanding Awementioning
confidence: 99%
See 1 more Smart Citation
“…Further research is required in order to understand what aspects of work environment and community and individual factors are important in the process of developing a positive self-appraisal of mental health that influences overall resilience. As previous research indicated (Chitra & Karunanidhi, 2021;Thompson, 2022), resiliencefocused training in policing mental wellness programming is effective and can support members of police services as well as the communities they serve. Practical changes in the delivery of mental health services will benefit from service users' direct input.…”
Section: Discussionmentioning
confidence: 95%
“…Often in policing studies, "resilience" has meant the absence of mental health symptoms (McCanlies et al, 2017) or a combination of other individual and social factors such as hardiness, optimism, sense of agency, etc. (Fyhn et al, 2015;Thompson, 2022). This study aims to facilitate an exploration among police services to identify pathways that can enhance their resilience on a collective and individual level.…”
Section: Resiliencementioning
confidence: 99%